ANALISIS KOLABORASI ANAK BERKEBUTUHAN KHUSUS (ABK) MELALUI KEGIATAN OUTBOUND PRAMUKA DI SDN 2 SIRNOBOYO - Wista Eka Priatna; Nely Indra Meifiani; Wulan Trisnawaty (Scholarly Journal of Elementary School, 2026)
Collaboration with children with special needs is the ability to work together in social activities. This ability can be developed through active involvement in activities such as scout outbound. This study aims to explore information related to the implementation of scouting activities designed to train children with special needs collaboration through scout outbound activities. This research also aims to find out the indicators that children with disabilities have in participating in scout outbound activities. This research is descriptive qualitative research with a case study approach. The subjects consisted of three children with disabilities who were selected through purposive sampling. Data were collected through observation, interviews and documentation. Data analysis used the Miles and Huberman model, namely data reduction, data presentation, and conclusion drawing. The results of the data analysis concluded that, firstly, scout outbound activities are effective in training collaboration between children with disabilities, as well as improving communication, responsibility and courage. Although there were obstacles such as difficulty focusing and waiting for their turn. Secondly, the five aspects of collaboration showed positive results. In general, the children's collaboration skills improved through active participation, supportive interactions and performing tasks according to role. Keywords: Collaboration, children with special needs, scout outbound.